Effect of duration of dystocia on haematobiochemical alterations in buff aloes - DHINDSA, S S; GANDOTRA, V K; NANDA, A S; SINGH, S P S; JINDAL, R; BRAR, P S (The Indian Journal of Animal Reproduction, 2023)
Dystocia leads to death of the dam and the calf especially in delayed cases. The present study was undertaken toassess certain haematobiochemical alterations in thirty three dystocia affected buffaloes, divided into four groups withlabour pains less than 12 hours (group A; n=07), 12-24 hours (group B; 11=12), 24-36 hours (group_C; n=06) or more than36 hours (group D; n=08). Haemoglobin (8.6-9.93 g/dl) and packed cell volume (30-36%) remained within the normalphysiological range in different groups. Glucose, insulin, blood urea nitrogen and creatinine concentrations increasedsignificantly from initial values of 98.77 mg/di, 8.25 mU/ml, 10.51 mg/di and 2.21 mg/di , respectively, in group A to180.22 mg/di, 61.03 mU/ml, 20.51 mg/di and 3.96 mg/di, respectively, in group D. Total plasma protein (5.72 g/dl) andplasma (4.36%) and blood (6.42%) volumes were significantly lower in group D as compared to other groups. It is concludedthat increased concentrations of blood urea nitrogen and creatinine and decreased circulatory volumes over the passage oftime in buffaloes following dystocia indicated the progression of dehydration and toxaemia in protracted cases.
Keywords: Buffalo; dehydration; dystocia; toxaemia